Pemberdayaan Masyarakat Melalui Wisata Edukasi dan Dampak yang Didapatkan Masyarakat Desa Pujonkidul - Hermawan, Yogi; Hidayatullah, Syarif; Alviana, Stella; Hermin, Dewi; Rachmadian, Aprilia (Perkumpulan Alumni dan Santri Mahyajatul Qurro’, 2021)
Educational tourism is a type of travel that aims to provide an overview, comparative research or knowledge of the field visited—this article made for study community empowerment through educational tourism and the impact of the Pujonkidul village community. Research conducted using a qualitative approach, namely research methods that go directly to the field to find data and the data obtained is the result of interviews and documentation. Stage’s analysis data that used researcher in research this is as following; collection data, Data reduction, Data presentation, and withdrawal conclusion. The results obtained from this study are that with the community empowerment program through educational tourism, the local community has a positive impact, especially in terms of the economy.